Identifikasi Endoparasit Pada Ikan Hasil Tangkap Sebagai Kandidat Ikan Domestikasi di Danau Lais Kota Palangka Raya - Rosita Rosita; Maryani Maryani; Revika Try Sela Manik; Toto Fransisco (Jurnal Akuakultur Sungai dan Danau, 2022)
The study aimed at determine the type of endoparasites in catch fish in Lake Lais Palangka Raya, Central Kalimantan which will later be used as candidate fish for domestication so that it can be used as a basis for determining attitudes and the next step in overcoming problems encountered in aquaculture activities examined at the Parasitology Laboratory Station. Fish Quarantine Quality Control and Safety of Fishery Products Palangka Raya. Examination of endoparasites is done by observing the internal organs by making a mucus smear which is examined under a microscope. From the results of the study, it was found that the dominant catches from the waters of Lake Lais were Toman fish (Channa micropeltes), Baung fish (Mystusnemurus), Gabus fish (Channa striata), Kerandang fish (Channa pleurophthalma) and 7 types of parasites were found in the caught fish. Dominating the waters of Lake Lais, namely Henneguya sp, Myxobolus sp, Senga sp, Philometra sp, Neoechinorhynchus sp, Cammalanus sp, Echinostoma sp.  The highest prevalence value in captured fish from Lake Lais is found in Toman fish, which is 100%, followed by Kerandang fish 90%, Cork fish 70% and the lowest prevalence value is in Baung fish, namely 50%, as well as the intensity value in fish. Toman is taller than other caught fish.